2008
DOI: 10.1016/j.jcmg.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Magnetic Resonance Imaging Estimation of Myocardial Iron to Left Ventricular Systolic and Diastolic Function in Thalassemia

Abstract: In patients with TDT, echocardiographic diastolic function parameters correlated poorly with EF and myocardial T2* and were thus not well-suited for risk stratification. Myocardial T2* had a strong relationship with EF and appears to be a promising approach for predicting the development of heart failure and for iron chelator dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 26 publications
5
44
0
1
Order By: Relevance
“…A major co-ordinated international effort is needed to continue to improve access to T2* CMR, although the provision of affordable and adequate transfusions and iron chelation therapy are primary issues. 5 Renzo Galanello, 6 Fabrice Danjou, 6 Gianluca Forni, 7 Antonis Kattamis, 8 Vassilis Ladis, 8 Marouso Drossou, 9 Demetra Vini, 9 Andreas Michos, 10 Vassilios Perifanis, 11 Tuncay Hazirolan, 12 Ana Almeida, 13 Yesim Aydinok, 14 Selen Bayraktaroglu, 14 Mirella Rangelova, 15 Denka Stoyanova, 16 Valeria Kaleva, 17 Georgi Tonev, 18 Amal El-Beshlawy, 19 Mohsen Elalfy, 20 Ibrahim Al-Nasser, 21 Wing-Yan Au, 22 Shau-Yin Ha, 22 Chi-Kong Li, 23 Winnie Chiu-Wing Chu, 23,24 Lee-Lee Chan, 25 Meng-Yao Lu, 26 Lia Wahidiyat, 27 Manuela Merelles-Pulcini, 28 Juliano de Lara Fernandes, 29 Fernando Kay, 30 P. Joy Ho, 31 Jane S. Hankins, 32 Maria Cappellini, 33 Shahina Daar, 34 Jameela Sathar, 35 Ali Taher, 36 George Kontoghiorges, 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major co-ordinated international effort is needed to continue to improve access to T2* CMR, although the provision of affordable and adequate transfusions and iron chelation therapy are primary issues. 5 Renzo Galanello, 6 Fabrice Danjou, 6 Gianluca Forni, 7 Antonis Kattamis, 8 Vassilis Ladis, 8 Marouso Drossou, 9 Demetra Vini, 9 Andreas Michos, 10 Vassilios Perifanis, 11 Tuncay Hazirolan, 12 Ana Almeida, 13 Yesim Aydinok, 14 Selen Bayraktaroglu, 14 Mirella Rangelova, 15 Denka Stoyanova, 16 Valeria Kaleva, 17 Georgi Tonev, 18 Amal El-Beshlawy, 19 Mohsen Elalfy, 20 Ibrahim Al-Nasser, 21 Wing-Yan Au, 22 Shau-Yin Ha, 22 Chi-Kong Li, 23 Winnie Chiu-Wing Chu, 23,24 Lee-Lee Chan, 25 Meng-Yao Lu, 26 Lia Wahidiyat, 27 Manuela Merelles-Pulcini, 28 Juliano de Lara Fernandes, 29 Fernando Kay, 30 P. Joy Ho, 31 Jane S. Hankins, 32 Maria Cappellini, 33 Shahina Daar, 34 Jameela Sathar, 35 Ali Taher, 36 George Kontoghiorges, 37 …”
Section: Discussionmentioning
confidence: 99%
“…5 Myocardial T2* is the only validated non-invasive measure of myocardial iron loading and is superior for this purpose to surrogates such as serum ferritin, liver iron, ventricular ejection fraction and tissue Doppler parameters. 3,[6][7][8][9][10] Although worldwide survival is still poor, 11 life expectancy is increasing in some countries with regular blood transfusion and well-managed iron chelation therapy. [12][13][14] In most cases, chronic myocardial siderosis is both preventable and reversible with modern chelation regimes.…”
Section: Introductionmentioning
confidence: 99%
“…At that stage, the treatment is difficult, and the prognosis is poor (9,22). In the literature, there are reported echocardiographic studies evaluating several functional and volumetric parameters in thalassemia patients (23,24). MRI techniques have recently been used to detect myocardial iron load and cardiac function (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these studies have demonstrated a significant correlation (25)(26)(27), others have not (11,28). The main limitation of TDI parameters is their dependence on heart rate.…”
Section: Discussionmentioning
confidence: 99%